Guru Pendidikan Agama Kristen Memiliki Peran Penting Dalam Menanamkan Nilai-Nilai Moral Dan Spiritual Kepada Peserta Didik Di Sekolah - Wiranto Wiranto; Lisa Sababalat; Sandra R Tapilaha (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Christian Religious Education Teachers Play a Vital Role in Building Moral and Spiritual Values of Students. This study reveals the importance of Christian Religious Education (CRE) teachers in instilling moral and spiritual values ​​in students at school. Using a qualitative approach, this research highlights how the teaching of religious principles by CRE teachers directly contributes to the formation of students' character. Beginning with the importance of character education in Indonesian education, especially through Christian Religious Education, the study continues by outlining interactive, contextual teaching strategies, and the role of teachers as positive examples. The research findings emphasize the effectiveness of these methods in instilling strong moral and spiritual values ​​in students, which are crucial for their character formation. This study highlights the significance of CRE teachers in character education and recommends further research to support effective teaching methods in Christian Religious Education within the school environment